Growth and body composition in Brazilian female rhythmic gymnastics athletes - Camargo, C. T. A.; Gomez-Campos, R. A.; Cossio-Bolaños, M. A.; De Oliveira Barbeta, V. J.; Arruda, M.; Guerra-Junior, G. (Journal of Sports Sciences, 2014)
The aim was to analyse the physical growth and body composition of rhythmic gymnastics athletes relative to their level of somatic maturation. This was a cross-sectional study of 136 athletes on 23 teams from Brazil. Mass, standing height and sitting height were measured. Fat-free and fat masses, body fat percentages and ages of the predicted peak height velocity (PHV) were calculated. The z scores for mass were negative during all ages according to both WHO and Brazilian references, and that for standing height were also negative for all ages according to WHO reference but only until 12 years old according to Brazilian reference. The mean age of the predicted PHV was 12.1 years. The mean mass, standing and sitting heights, body fat percentage, fat-free mass and fat mass increased significantly until 4 to 5 years after the age of the PHV. Menarche was reached in only 26% of these athletes and mean age was 13.2 years. The mass was below the national reference standards, and the standing height was below only for the international reference, but they also had late recovery of mass and standing height during puberty. In conclusion, these athletes had a potential to gain mass and standing height several years after PHV, indicating late maturation.